2012
DOI: 10.1097/ico.0b013e31823cbecb
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pterygium Recurrence Rates After Limbal Conjunctival Autograft Transplantation and Other Techniques

Abstract: According to the current evidence from literature, recurrence rates after pterygium excision with LCAG are lower when compared with the use of bare sclera, bulbar conjunctival autograft, or intraoperative mitomycin C. Although recurrence rates of LCAG were similar to the amniotic membrane graft, further large-scale randomized controlled trials would be required to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 27 publications
1
31
0
5
Order By: Relevance
“…[10][11][12] In our study, we found that vessels around pinguecula regressed after excision of the pinguecula. Regression presumably occurs because we have removed an inflammatory nidus in the pinguecula, be it for biological and/or mechanical reasons.…”
Section: Discussionmentioning
confidence: 74%
“…[10][11][12] In our study, we found that vessels around pinguecula regressed after excision of the pinguecula. Regression presumably occurs because we have removed an inflammatory nidus in the pinguecula, be it for biological and/or mechanical reasons.…”
Section: Discussionmentioning
confidence: 74%
“…Tüm bu yöntemleri nüks açısından karşılaştıran Zheng K ve ark. 'nın yaptıkları bir çalışmada konjonktivalimbal otogreft transplantasyonunun açık sklera, konjonktival otogreft transplantasyonu ve mitomosin C uygulamasına göre daha düşük nükse yol açarken, amniotik membran transplantasyonu ile aynı oranda nükse yol açtığı görülmüştür [19]. Ancak mitomisin C'ye bağlı ciddi komplikasyonlar bildirilmesi, amniotik membranın elde edilmesinin ve alıcı yatağa sütüre edilmesindeki güçlükler otogreft yöntemleri-ni ön plana çıkarmıştır.…”
Section: Discussionunclassified
“…Başarılı tedavinin ana hedefleri pterjium dokusunu en etkin ve güvenilir yöntemle çıkartmak, görme keskinliğini arttırmak ve nüksü önlemektir [4].…”
Section: Introductionunclassified
“…Bugün için pterjium tedavisinde primer kapama tekniği, mitomisin C, beta ışını uygulaması, antianjiojenik ajanlar ya da defektin konjonktival otogreft veya amniyotik membranla örtülmesi ve bunların kombinasyonları kullanılmaktadır [4].…”
Section: Introductionunclassified